2017
DOI: 10.1002/ejic.201700210
|View full text |Cite
|
Sign up to set email alerts
|

(Aminomethylene)phosphonate Analogues as ZnII Chelators: Synthesis and Characterization

Abstract: TOC

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Heterocyclic moieties such as the imidazolyl group mimic histidine, which is known as the best amino acid ligand for Cu­(II) and Zn­(II) ions in proteins and peptides . Indeed, we recently reported that AMP-(Im) 2 forms a most stable complex with Zn­(II) (log β = 22) . AMP-(Im) 2 was synthesized by formation of an intermediate Schiff base from imidazolyl aldehyde and AMPA followed by Schiff base reduction by 2-picoline-borane.…”
Section: Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Heterocyclic moieties such as the imidazolyl group mimic histidine, which is known as the best amino acid ligand for Cu­(II) and Zn­(II) ions in proteins and peptides . Indeed, we recently reported that AMP-(Im) 2 forms a most stable complex with Zn­(II) (log β = 22) . AMP-(Im) 2 was synthesized by formation of an intermediate Schiff base from imidazolyl aldehyde and AMPA followed by Schiff base reduction by 2-picoline-borane.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Moreover, ligands with soft binding sites (e.g., N-heterocycles, thiols, or those with π-bonds) usually form stronger complexes with Cu­(II) than with Zn­(II) . Although AMPA analogues 3–9 formed strong complexes with Zn­(II) with log K values from 6.69 to 12.68, AMP-Th formed the least stable Zn­(II) complex, with the lowest log K value, 6.69 . In this study, we determined the stability constants for Cu­(II)-AMP-Th and Cu­(II)-AMP-(Im) 2 complexes by potentiometric pH titration.…”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations